P33 Patient/parent acceptability of different forms of oral hydrocortisone in congenital adrenal hyperplasia. Issue 5 (19th April 2023) - Duncan, Jennifer; Bracken, Louise; Seddon, Gabrielle; Hill, Amy; Nuttall, Amy; Clarke, Ellie; Blundell, Pauline; Madine, Sarah; Gill, Andrea
Abstract : Aim: Hydrocortisone is used in Congenital Adrenal Hyperplasia (CAH) as a long-term replacement therapy. Accurate dosing, patient acceptability, and ease of administration of the available dosage forms are vital as treatment is life-long. 1 Prior to the introduction of a licensed immediate-release formulation the use of a variety of unlicensed oral hydrocortisone preparations was widespread. This project aimed to explore patient/parent acceptability of oral hydrocortisone preparations in the real-world setting. This included assessment of preferences and the reasons for discontinuation if more than one formulation had been used. Method: This clinical audit was registered within the Trust. Two e-surveys were developed by a multi-disciplinary team (MDT) using Microsoft Forms, one for parents of children <8 years and the other for parents and children ≥8 years. With permission, both e-surveys included the validated Pediatric Oral Medicines Acceptability Questionnaire for caregivers (POMAQ-C) and the POMAQ-P was optional for patients ≥8 years old. 2 Most questions utilised the Likert rating scale, with 5 being positive and 1 being negative. The form was piloted with one family, then parents were contacted by the clinical team and if happy to take part, a member of the project team contacted them with the survey link details. Inclusion criteria: Patients with CAH aged 6 months to 17 years (inclusive) taking an oral form of hydrocortisone. Exclusion criteria: non-UK residents, non-English speaking, non-classical CAH patients, and/or not taking an oral form of hydrocortisone. Results: 33 eligible patients were identified. The results below represent the findings from the first 8 families. Patients were aged between 1 to 17 (mean 7.7) years. Three (37.5%) were taking hydrocortisone tablets, one (12.5%) was taking Alkindi® granules, and four (50%) hydrocortisone liquid. The mean score for parent-rated overall acceptability of tablets, granules, and liquid preparations was 4.3, 4, and 4.75, respectively. Parent-rated mean acceptability score for their child was 4.67, 3, and 5, respectively for the different types of formulations. One patient had moved from liquid hydrocortisone to tablets due to problems obtaining prescriptions and transporting/refrigerating the product when not at home. Another had moved from granules to liquid as the parent found it 'difficult to give to a baby' and reported issues obtaining a prescription. Conclusion: Assessment of the acceptability of medicines for children in a real-world setting is possible and allows for parents/carers and patients to provide practical feedback on available treatment options. To date, parental feedback received indicates a slight preference for liquids over tablet and granule hydrocortisone formulations, although data is currently limited. References: Boulos N. Formulation matters: safe oral hydrocortisone use in children. The Pharmaceutical Journal December 2021;No 7956;307(7956). Turner-Bowker DM, An Haack K, Krohe M, et al . Development and content validation of the pediatric oral medicines acceptability questionnaires (P-OMAQ): patient-reported and caregiver-reported outcome measures. Journal of Patient-Reported Outcomes 2020;4 (1).